INDIVIDUALISM IN GADGET ERA: HAPPINESS AMONG GENERATION X,Y,Z - Abror, Robby Habiba; Sofia, Nanum; Sure, Suci Ramadhani (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to see the happiness that existed in generations X, Y, and Z in the era of gadgets. Each generation has its own source of happiness. Gadgets, as one of the results of rapid technological progress, allegedly become one of the benchmarks of the increase of new happiness, because it is able to penetrate the boundaries of space and time. However, the sophistication of gadgets with a variety of features and devices not only implicate positively, but also negative. Positively, gadgets are able to tighten social interactions, but also have a negative impact, especially making the person engrossed with their own world. Although sitting together, people often no longer greet each other because they prefer gadgets. Individualistic behavior begins to develop in the current gadget era. For this reason, this research would like to see the happiness of three generations that influenced by the culture of individualism.